The Growing HIV Infections in Pakistan: Implications and Future Prospects - Iqbal, Muhammad Naeem; Shahzad, Mirza Imran (International Journal of Molecular Microbiology, 2023)
The incidence of new cases of HIV infection has decreased recently in the world’s most HIV-burdened regions. A nation with economic problems, a poor literacy rate, and lack of appropriate health standards is more susceptible to the effects of diseases like HIV. The spread of HIV continues to be one of the biggest problems affecting people’s social and economic life as well as their health in Pakistan. This article describes the present state of HIV infections and the difficulties in containing the virus. Addressing HIV prevention and sustaining treatment is vital to improving the population health and the economic well-being of the country. There is a need for integrated preventative measures that requires other sectors outside health to play a critical role.